2016
DOI: 10.15560/12.6.1993
|View full text |Cite
|
Sign up to set email alerts
|

Spiroxys contortus (Rudolphi, 1819) and Hedruris orestiae (Moniez, 1889) in Argentine turtles

Abstract: Knowledge of parasites in turtles is scarce, particularly with regard to freshwater turtles of South America. Here, we describe the association of Spiroxys contortus (Rudolphi, 1819)in Phrynops hilarii (Duméril & Bibron, 1835) and S. contortus and Hedruris orestiae (Moniez, 1889) in Hydromedusa tectifera (Cope, 1870). The presence of S. contortus in P. hilarii represents a new host record and also the southernmost geographic record for this species. More interestingly, the presence of H. orestiae in H. tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 1 publication
0
15
0
2
Order By: Relevance
“…These results contrast with Palumbo et al . (2016), who found only H. orestiae in Hyd. tectifera in a stream 100 km away from the study area of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results contrast with Palumbo et al . (2016), who found only H. orestiae in Hyd. tectifera in a stream 100 km away from the study area of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the Neotropical region, nine species of Hedruris were recorded: H. siredonis Baird, 1858, H. orestiae Moniez, 1889, H. mucronifer Schuurmans Stekhoven, 1951, H. basilichtensis Mateo, 1971, H. juninensis Bendezú, 1976, H. moniezi Ibañez & Córdova, 1976, H. heyeri Bursey & Goldberg, 2007, H. suttonae Brugni & Viozzi, 2010 and H. bifida Rossin & Timi, 2016. Among them, only H. mucronifer , H. suttonae , H. bifida and H. orestiae occur in Argentina (Bursey & Goldberg, 2000; Palumbo et al ., 2016; Rossin & Timi, 2016; Serrano-Martinez et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on helminths that parasitize freshwater turtles of family Chelidae in South America were conducted in Brazil (Freitas & Dobbin Jr., 1971;Vieira et al, 2008;Ávila et al, 2010;Bernardon et al, 2013;Novelli et al, 2013;Mascarenhas et al, 2013;Silva, 2014;Novelli et al, 2014;Vieira et al, 2016;Mascarenhas et al, 2016;, Argentina (Lombardero & Moriena, 1977;Palumbo et al, 2016), and Uruguay (Cordero, 1946;Mañé-Garzón & Gil, 1961a, b, c, d;Mañé-Garzón & Gil, 1962a, b;Brooks & Holcman, 1993). In Brazil, digenetics (Bernardon et al, 2013;Mascarenhas et al, 2016) and nematodes (Bernardon et al, 2013;Mascarenhas et al, 2013 were reported parasitizing the Acanthochelys spixii (Duméril & Bibron, 1835), Hydromedusa tectifera Cope, 1870 and Phrynops hilarii (Duméril & Bibron, 1835).…”
mentioning
confidence: 99%
“…The parasitological index, prevalence, mean intensity, and mean abundance of infection were estimated according to Bush et al (1997). Notes: Spiroxys contortus was recorded in Argentina parasitizing P. hilarii with prevalence (P) of 70% and mean intensity of infection (MII) of 3 helminths/host and H. tectifera with P = 70% and MII = 1.7 helminths/host (Palumbo et al, 2016). In Brazil, the species was registered in H. tectifera with MII of 14.2 helminths/host (Mascarenhas et al, 2013) and T. dorbigni with MII of 70.17 helminths/host (Mascarenhas & Müller, 2015a).…”
mentioning
confidence: 99%